Espaços e territorialidades do “festejar” da Catira no estado de Goiás - Teixeira, Maisa França (2012)
The present study describe and analyze the construction of cultural and territorial identity that originates the formation of territoriality in Goiás traditions, the case of the dances of catira. The study will allow to reflect on the following phenomenos: the state of Goiás has an identity catirana? How to identify the basis that guarantee the existence of the territorial identity of catira? It is unreasonable affirmate that in the state of Goiás, the territoriality of the manifestation of catira present themselves in different ways producing symbols and meanings that gives sense to the space and local culture? How do these dances become symbolic elements that mark a territorial basis? What is the relationship between the body and embodiment in the dance? catira is referenced continously and with a creatively form through the artistic languages, memories, narratives, images and cultural expressions in the Goiás festivals. This study should be understood as a way to recognize and elicit the production of cultural identity, theirs influences and diversity created into the territory analyzed, and discuss the territorial dimensions built for the dance. The methodological procedures are aggregated into a set of sources and data, witch obtained through literature searches and field. It has been adopted as a reference, the cultural approach to Human Geography for this study. The qualifications earned at the social subjects are supported in the groups analyzeds in the oral history, in the observation and also, in the interviews makeds. The photographic records will be refers in this research of the manifestation of catira. The spatial area of the study involves three cities of the Goiás: Anápolis/GO, Silvânia/GO e São João D’Aliança/GO, respectively because of the due the years of existence, the recognition in nacional and internacional and the different festivals of presentations. In each of these locations were investigates respectively the groups of Catira: Irmãos Floriano, Água Branca e Aliança. As part of the results, it becomes possible to recognize that the dances discussed promove a inicial form of construction the identities catiranas in Goiás. Futhermore in this study shows these dances promove individual and collective identities that provide the territorialities that consist in the process of reinterpretation of the language, body and memory and reconstructed, allowing in this new meanings.